The grapevine VvibZIPC22 transcription factor is involved in the regulation of flavonoid biosynthesis - Malacarne, Giulia; Coller, Emanuela; Czemmel, Stefan; Vrhovsek, Urska; Engelen, Kristof; Goremykin, Vadim; Bogs, Jochen; Moser, Claudio (The journal of experimental botany, 2016)
Highlight. Functional analysis of the grapevine VvibZIPC22 indicates that this factor is involved in the regulation of different branches of the flavonoid path